Siloed funding of multibenefit projects highlights the need for funding programs that integrate cobenefits - Grimm, Marie; Serra-Llobet, Anna; Bruce, Molly; Kiparsky, Michael (Frontiers in Water, 2025)
Multibenefit projects, such as integrated flood risk management projects, are gaining attention as solutions for complex social and environmental challenges. Among other benefits, these projects offer opportunities to combine flood risk reduction, restoration, and climate resilience. However, multibenefit projects face institutional challenges to their implementation. One such challenge is securing adequate and sustained funding, partly because of a mismatch between the integrative goals of multibenefit projects and the narrower intent of siloed funding sources structured largely in response to the funding needs of traditional, single-purpose gray infrastructure projects. We explore how proponents can fund multibenefit projects and what the funding landscape means for project implementation. Using the Pajaro River flood risk management project in California as a case study, we analyze the project’s funding sources and implications for cobenefits. We explore how project proponents are navigating a single-purpose flood risk management project authorization and a fragmented funding landscape to achieve benefits beyond flood risk reduction. Using thematic document analysis and consultations with local project partners, we outline pursued benefits, funding sources, and funding gaps. In our case study, motivated champions incorporated cobenefits like groundwater recharge and habitat restoration into the project, despite narrow funding provisions and a single-purpose project authorization. However, narrow funding provisions challenged these efforts, causing some funding gaps for cobenefits. To address these challenges, agencies can provide funding programs that reflect the integrated nature of many climate solutions and encourage cobenefits, rather than rely on champions to incorporate such considerations. If decision-makers want multibenefit solutions across sectors, agencies need to provide funding consistent with the integrated nature of these challenges and promote, rather than stifle, the pursuit of cobenefits. While institutional, jurisdictional, and administrative challenges to funding multibenefit projects are currently tackled by individuals on a project-by-project basis, a broader effort to reform funding regimes could ease these burdens and scale up integrated solutions.